Improved System Information on the Job Training (SIOJT) Based on System Development to Improve Services at the Air Transportation HR Development Center - Ratri Ratri; Ahmad Bahrawi (Budapest International Research and Critics University, 2021)
The Air Transportation Human Resources Development Center (PPSDMPU) needs changes in the implementation of services, both services that directly intersect with the community or which are services to the agency itself and agency partners. In this Action Change, services are provided to their agencies, namely the Air Transportation HR Development Center (PPSDMPU), Aviation Polytechnic, and also to stakeholders (Airnav Indonesia, PT. Angkasa Pura I (Persero), PT. Angkasa Pura II (Persero), Implementing Units Airport/ UPBU) and Directorate of Aviation Navigation. Services related to the Development of the OJT Information System (SiOJT) which have been regulated in the OJT Guidelines have been ratified in the Decree of the Head of the Air Transportation HR Development Center.